PERAN KEPALA KANTOR URUSAN AGAMA KECAMATAN TASIKMADU KABUPATEN KARANGANYAR DALAM MENANGGULANGI PERKAWINAN DIBAWAH UMUR - Abubakar, Kirana; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2024)
The main problem in this study is related to underage marriage that occurs in the Tasikmadu sub-district, along with how to overcome it carried out by the Head of KUA in minimizing underage marriage. This study aims to determine (1) the condition of underage marriage in Tasikmadu District, Karanganyar Regency, (2) The Role of the Head of the Office of Religious Affairs in preventing underage marriage. This research uses qualitative methods. Qualitative research is a continuous research process so that the data collection and data analysis stages are carried out simultaneously during the research process. Data collection was carried out by interview method to the Head of KUA Tasikmadu. The location of the research was carried out at the Office of Religious Affairs in Tasikmadu District, Karanganyar Regency. The results of research conducted at the Office of Religious Affairs of Tasikmadu District, Karanganyar Regency are factors that cause underage marriage to occur, there are also reasons that cause underage marriage that often occurs in the community of Tasikmadu District, Karanganyar Regency are economic factors, factors that have loved each other, parental factors and the most important factor is pregnancy out of wedlock. The role of the Office of Religious Affairs in tackling underage marriage has been carried out in accordance with the procedure, namely by conducting socialization to the community through routine studies related to marriage, besides that the KUA also conducts socialization through premarital guidance for teenagers how to build a good household. Implementation of the marriage law regarding the age limit for marriage and in cooperation with youth leaders and village officials or other agencies.